Penerapan Strategi City Branding Kabupaten Ponorogo "Ethnic Art of Java" - Megantari, Krisna (ARISTO, 2019)
This research is expected to be one of the mapping models of communication strategy problems, especially the study of city branding strategies. It is expected that the outcome obtained is to measure how a city can explore its tourism potential and then become an iconic city. The city branding strategy is a new study in the world of tourism that is closely related to the development of communication technology in synergy with marketing tourism. It cannot be denied that the city branding strategy is closely related to tourism development strategies. Because the end of the success of city branding is an increase in foreign exchange in a city. It is hoped that with this research, Ponorogo regency can clearly map the original tourism potential of the region and the city branding echoes of Ponorogo Regency will be increasingly familiar to the eyes of the Indonesian and foreign communities. Keyword: Communication Strategy; City Branding; Ethnic Art of Java; Tourism;